HIV-1 Accessory Protein Vpu Internalizes Cell-surface BST-2/Tetherin through Transmembrane Interactions Leading to Lysosomes - Iwabu, Yukie; Fujita, Hideaki; Kinomoto, Masanobu; Kaneko, Keiko; Ishizaka, Yukihito; Tanaka, Yoshitaka; Sata, Tetsutaro; Tokunaga, Kenzo (The Journal of biological chemistry, 2009)
Bone marrow stromal antigen 2 (BST-2, also known as tetherin) is a recently identified interferon-inducible host restriction factor that can block the production of enveloped viruses by trapping virus particles at the cell surface. This antiviral effect is counteracted by the human immunodeficiency virus type 1 (HIV-1) accessory protein viral protein U (Vpu). Here we show that HIV-1 Vpu physically interacts with BST-2 through their mutual transmembrane domains and leads to the degradation of this host factor via a lysosomal, not proteasomal, pathway. The degradation is partially controlled by a cellular protein, β-transducin repeat-containing protein (βTrCP), which is known to be required for the Vpu-induced degradation of CD4. Importantly, targeting of BST-2 by Vpu occurs at the plasma membrane followed by the active internalization of this host protein by Vpu independently of constitutive endocytosis. Thus, the primary site of action of Vpu is the plasma membrane, where Vpu targets and internalizes cell-surface BST-2 through transmembrane interactions, leading to lysosomal degradation, partially in a βTrCP-dependent manner. Also, we propose the following configuration of BST-2 in tethering virions to the cell surface; each of the dimerized BST-2 molecules acts as a bridge between viral and cell membranes.